Condom use with random partners by users of testing and counseling center in STD/AIDS - Canário, Djulian Diego Ribeiro do Carmo; Santos, Kamila Juliana da Silva; Davoglio, Rosane Silvia; Segundo, Flávio Laranjeira Ferraz; Gomes, Ana Vitória Teixeira de Medeiros; Nascimento, Ananda Ariane Januário do; Conceição, Karoline Barros; Araújo, Jéssica de Sá; Neves, Linda Kelly de Oliveira (Brazilian Journal of Sexually Transmitted Diseases, 2013)
Introduction: Among the main situations of vulnerability to HIV and other sexually transmitted diseases (STD), the lack of condom use with non-fixed partners is a major problem, which affects men and women, regardless of age or marital status. Objective: To characterize the users of the Center for Counseling and Testing STD/AIDS in Juazeiro, Bahia, Brazil, whose have non-fixed partners; and to determine the prevalence of condom use in the year 2011. Methods: We developed a descriptive study using secondary data from the health service, using the Entry Form Information System of the Center for Counseling and Testing, with a global number of 408 users. In data analysis, we evaluated the distribution of variables by means of absolute and relative frequency. Results: The majority of participants were male, aged between 21–35 years with 8 years or more of schooling and about a third of them had a stable partner. The prevalence of condom use with a non-fixed partner was low (35.29%), increasing according to the schooling years. The customary use was more common among gays and bisexuals. Of those who reported having any type of STD in the past year, about 70% reported using condoms only sometimes or never. Conclusion: The use of condoms with non-fixed partners among these users is not common, being observed unsafe sexual practices that expose them and their partners at a greater risk of contamination by DST.